A rare presentation of hyperhomocysteinemia and folate deciency asCSVT in young male - Shetty Mallikarjun; Kamal Hassan; B Prahlad; Basawaraj Puranic (International Journal of Medical Research and Review, 2022)
Introduction: Cerebral sinus venous thrombosis (CSVT) is a relatively rare, potentially fatalneurological condition that can be frequently overlooked due to its vague nature and its variedspectrum of clinical presentation. It’s a multifactorial condition with gender-related specific causes.It’s a rare form of venous thromboembolism representing almost 0.5-3 % of all types of stroke,affecting predominantly younger people, and females three times more commonly affected thanmales. Incidents in adults are 3- 4 million. The diagnosis of CSVT is becoming easier now days dueto advanced neuroimaging techniques. Abnormality in the thrombophilic profile is associated withenhanced risk of CSVT. It has varied etiologies such as the Hypercoagulable States (inherited) that ishyperhomocysteinemia, protein C and protein S deficiency, Antithrombin-III deficiency, Factor Vleiden mutations, autoimmune causes. Other acquired causes like CNS infection, trauma,dehydration, pregnancy, substances abuse and oral contraceptives.